Agent-based approach for analysis of electricity distribution technological processes in power systems - Kostinskiy, S S; Mokhov, V A; Kruglova, T N; Shaikhutdinov, D V; Vlasov, A S (IOP conference series. Materials Science and Engineering, 2019)
The question of minimizing the loss of the active component of power in power transformers of distribution networks is considered.Authors' attention is focused on the reduction of additional losses due to the non-sinusoidal nature of the load. The proposed solution is based on the application of the principle of level decomposition for the system "digital substation - distribution network". There are three logical levels distinguished, which are described in terms of the agent approach within the framework of this system. At the single-phase consumer level the solution of the combinatorial problem of dynamic connection of consumers by means of agent metaheuristics is offered. It is proposed to integrate an intelligent agent into the transformer substation. The main functions of the agent are to control the launch of agent metaheu-ristics and adaptive filtering of higher harmonic components of the current. Also, the integration of an intelligent agent is offered at the digital substation level. Its task is to synthesize a new configuration of the distribution network, subject to receiving information from agents of transformer substations. For the coordinated work of all agents, the organization of their interaction through a wireless network is proposed.